Revitalisasi Peran Kelompok Wanita Tani Jempiring dalam Pelestarian Kuliner Upakara melalui Pembuatan Jajan Tradisional Uli dan Begina di Desa Bresela : Empowering the Jempiring Women Farmers’ Collective in the Custodianship of Upakara Culinary Heritage through the Time-Honoured Craft of Uli and Begina in Bresela Village - AP, Yuhendra; I Wayan Sweca Yasa; A.A. Made Semariyani; Luh Suriati; Ni Made Ayu Suardani; I Gede Pasek Mangku; Ni Luh Putu Putri Setianingsih; I Wayan Sudiarta; M. Aditya Prayoga; Muhammad Zahran Rasyid Sulaeman (Universitas Mataram, 2025)
This public beneficence program was designed to preserve traditional Balinese culinary heritage while simultaneously empowering rural women economically. The main target of this initiative was the Jempiring Women Farmer Group (KWT) in Bresela Village, Payangan District, Gianyar Regency, Bali. The focus of the program was to train participants in the production of two traditional ceremonial snacks, jajan uli and jajan begina, which are essential offerings in Balinese religious rituals. These traditional snacks carry deep symbolic meaning and are still widely used in local ceremonies. The training took place on June 15, 2025, and applied a participatory approach that combined knowledge sharing, hands-on practice, and product evaluation. As a result, the participants improved their skills in selecting quality ingredients, applying hygienic food processing methods, and maintaining the traditional form and symbolism of the snacks. Beyond enhancing technical abilities, the program also opened up entrepreneurial opportunities by integrating traditional cultural practices with home-based economic development. This activity successfully fostered local knowledge, cultural sustainability, and the economic empowerment of women in the rural community.